Characterization of Sintered Hydroxyapatite samples produced by 3D printing. Issue 5 (19th August 2014) - Pires, Inês; Gouveia, Bárbara; Rodrigues, Jorge; Fonte, Ruben; Campbell, R. Ian; Campbell, R. Ian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This study is part of a project concerned with the fabrication of calcium phosphates implants by 3D printing. However, before considering a more complex structure, like scaffolds or implants, a thorough knowledge of the role played by the sintering temperature on physical and mechanical the properties of porous hydroxyapatite (HA) is necessary. Design/methodology/approach The characteristics of sintered HA samples have be analyzed by means of x-ray diffraction, SEM and uniaxial compression tests. The 3D printing parameters used to produce the HA samples were those who led to higher accuracy and mechanical stability. Findings Sintering temperature and powder morphology are critical factors influencing densification behavior, porosity, phase stability, mechanical strength and tangent modulus of the HA samples produced by 3D printing. This study allowed to conclude about the 3D printing parameters to be use to produce porous hydroxyapatite specimens with the required integrity and dimensional accuracy, and the optimal post-processing sintering temperature which led to the best results in terms of porosity, microstructure, phase stability of HA and mechanical properties. Originality/value This paper provides a method to evaluate the manufacturability of calcium phosphate models produced by 3D printing.